THE ROLE OF PSYCHOLOGICAL SERVICES IN EARLY CHILDHOOD DEVELOPMENT AND WAYS TO IMPROVE THEM (Web of Teachers: Inderscience Research, 2025)
This article explores the essential role of psychological services in early childhood development, highlighting the need for timely and professional psychological support in ensuring the emotional, cognitive, and social well-being of children. It also discusses various strategies to enhance these services to meet the evolving needs of modern educational and developmental systems. Special attention is given to the implementation of psychological practices, the integration of services into educational policy, and the potential of digital and community-based innovations in broadening accessibility.